Association between Tomato and Lycopene Consumption and Risk of All‐Cause and Cause‐Specific Mortality: Korean Genome and Epidemiology Study Cohort. Issue 4 (26th January 2023) - Jung, Hyein; Shin, Sangah
Abstract : Scope: Tomato has well‐known beneficial health effects and is an important source of lycopene. The study aims to clarify the evidence for the association between tomato and lycopene consumption and all‐cause and cause‐specific mortality in Korean adults. Methods and results: Data analyzed in the current study are obtained from the Korean Genome and Epidemiology Study Cohort. Mortality outcomes are determined based on death records from 2001 to 2020. Tomato and lycopene consumption is assessed using food frequency questionnaires and antioxidant databases and divided into quintiles. Over a mean follow‐up of 11.5 years, 5863 deaths are recorded among 139913 participants aged over 40 years. Tomato consumption is not associated with the risk of all‐cause and cancer mortality. However, the highest tomato consumption group has a lower risk of cardiovascular disease (CVD) mortality (HR = 0.779; 95% CI = 0.633, 0.957). Lycopene consumption is inversely associated with all‐cause (HR = 0.872; 95% CI = 0.801, 0.950), and CVD (HR = 0.680; 95% CI = 0.548, 0.845) mortality. Conclusion: A higher intake of tomatoes and lycopene is inversely related to the risk of CVD mortality, and lycopene consumption is associated with a lower risk of all‐cause mortality. Abstract : In this study including 139913 participants aged over 40 years from three prospective cohort studies in South Korea, higher tomato consumption is associated with a lower risk of cardiovascular disease mortality (22%), and lycopene consumption is associated with a lower risk of all‐cause (13%) and cardiovascular disease mortality (32%).